2021
DOI: 10.3390/ijerph18030982
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Coping Strategies in Police Officers: A Quantitative-Qualitative Pilot Study

Abstract: Background. Because of their work, emergency workers, such as police officers (POs), are exposed to traumatic events on a daily basis. These experiences can have consequences in terms of physical and emotional stress. Primary attachment relationships affect the development of coping strategies for dealing with stressful events (primarily hyperactivating strategies in entangled adults and hypo-activating strategies in dismissing adults). In this study, we explored how POs describe the experience of traumatic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 66 publications
(74 reference statements)
4
22
0
1
Order By: Relevance
“…Similar to experiences reported by police officers (Civilotti et al, 2021;Perez et al, 2010), therapists (Bell, 2003;Pistorius et al, 2008) researchers (Moran & Asquith, 2020) and lawyers (Weir et al, 2020) working with PTM, Crown prosecutors reported experiencing an array of VT symptoms e.g. sleep disturbances, suspicion, paranoia and hypervigilance in the safety of themselves and also loved ones.…”
Section: Research Question One: What Are Crown Prosecutors' Experiences Of Working With Ptm?supporting
confidence: 57%
“…Similar to experiences reported by police officers (Civilotti et al, 2021;Perez et al, 2010), therapists (Bell, 2003;Pistorius et al, 2008) researchers (Moran & Asquith, 2020) and lawyers (Weir et al, 2020) working with PTM, Crown prosecutors reported experiencing an array of VT symptoms e.g. sleep disturbances, suspicion, paranoia and hypervigilance in the safety of themselves and also loved ones.…”
Section: Research Question One: What Are Crown Prosecutors' Experiences Of Working With Ptm?supporting
confidence: 57%
“…On a clinical level, as indicated by Ahmad et al [44] and by Civilotti et al [121], it is important to consider the capacity to recognize positive and negative cognitions and emotions rooted in the development stage and the sociocultural context of the child or adolescent. Some deviations from the standard EMDR protocol are necessary in recalling traumatic events, for example, when identifying negative cognitions and emotions and especially in the identification of positive cognitions.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to pay attention to the psychological stress they encounter during their work. A number of authors point to the psychological burden posed to police officers during their work [ 53 , 54 ]. Mental workload must not be underestimated, as it may affect the police even after work [ 6 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%